2014
DOI: 10.3109/09638288.2014.915348
|View full text |Cite
|
Sign up to set email alerts
|

“It’s fun, but …” Children with cerebral palsy and their experiences of participation in physical activities

Abstract: Asking children with CP about the physical activities they enjoy, and giving them the opportunity of trying self-selected activities with the right support is important for facilitating an increased participation in physical activities. Having fun with family and friends when being physically active, and enjoying the sensation of speed should be taken into consideration when designing interventions. When supporting children to become and remain physically active, attention should be paid to pain, fatigue and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 27 publications
3
62
0
1
Order By: Relevance
“…Previous studies about the situation for young disabled people at school or in physical activity in general (Asbjørnslett & Hemmingsson, 2008;Barron, 1996;Bredahl, 2013;Gaskin, Andersen, & Morris, 2012;Lauruschkus, Hallström, & Nordmark, 2015;Taub & Greer, 2000) or in PE per se (Fitzgerald, 2005;Fitzgerald & Stride, 2012;van Amsterdam, Knoppers, & Jongmans, 2015) have shown that disabled students often feel excluded, singled out and picked on during lessons in PE. The 'visibility' of bodies and abilities during the lessons and in the dressing and shower rooms, with the ensuing experience of vulnerability, is underlined (Barron, 1995;Bredahl, 2013;Fitzgerald & Stride, 2012).…”
Section: (Dis)ability and Pementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies about the situation for young disabled people at school or in physical activity in general (Asbjørnslett & Hemmingsson, 2008;Barron, 1996;Bredahl, 2013;Gaskin, Andersen, & Morris, 2012;Lauruschkus, Hallström, & Nordmark, 2015;Taub & Greer, 2000) or in PE per se (Fitzgerald, 2005;Fitzgerald & Stride, 2012;van Amsterdam, Knoppers, & Jongmans, 2015) have shown that disabled students often feel excluded, singled out and picked on during lessons in PE. The 'visibility' of bodies and abilities during the lessons and in the dressing and shower rooms, with the ensuing experience of vulnerability, is underlined (Barron, 1995;Bredahl, 2013;Fitzgerald & Stride, 2012).…”
Section: (Dis)ability and Pementioning
confidence: 99%
“…Disabled students tell about classmates who do not accept them, call them names, stare at them or make fun of their capacities during the physical activity. They have experiences of not being chosen when teams are formed, and of classmates that do not pass them the ball when playing team games (Brittain, 2004;Fitzgerald, 2005;Fitzgerald & Stride, 2012;Lauruschkus et al, 2015). These negative experiences may give rise to feelings of difference and inferiority (Gaskin et al, 2012), thus affecting other parts of the disabled students' life, and can lead to avoidance of physical activity outside school and as an adult (Brittain, 2004;Fitzgerald & Stride, 2012;Gaskin et al, 2012).…”
Section: (Dis)ability and Pementioning
confidence: 99%
“…Predictably, 100,191 some parents reported that their boys were increasingly frustrated at the loss of function (see Perceived improvement in confidence, independence or participation) and consequent withdrawal from sport, play (d880) and their peer group (d7500).…”
Section: Participation Restrictionmentioning
confidence: 99%
“…Young people with cerebral palsy (CP) often report that they want to be more physically active, but acknowledge pain and fatigue as barriers to participation. 1 With regard to cognitive and academic function, pain and fatigue have been documented to partially mediate the relationship between topographical severity and performance at school in children with CP. 2 Fatigue is not unique to children; adults with spastic diplegic CP report significantly higher levels of fatigue and pain than unaffected adults.…”
mentioning
confidence: 99%
“…This is true not only of children and adolescents who are developing typically; but, and perhaps more importantly, it is also true for individuals with developmental disabilities such as cerebral palsy (CP). 1 In addition, clinicians have long recognized the importance of physical activity for individuals with CP; yet increasing participation in such activities has been a difficult task, in part due to the development of secondary musculoskeletal conditions such as increased fatigue and pain that may be related to being active. 2 In a recent qualitative study, individuals with CP described difficulty with predicting and managing fatigue from activities of daily living such as walking.…”
mentioning
confidence: 99%